Democracy and the challenge of globalisation in India - Mitra, Subrata Kumar (The Indian journal of political science, 2001)
The contemporary commitment to the spread of democracy and human rights has greatly helped to give explicit shape to the internal contradiction of globalisation, which derives from its essential liminality. Globalisation seen from the respective contexts of developed and changing societies evokes contradictory expectations and images. The main objective of this essay is to present some evidence of these contradictory images that characterise the discourse of globalisation in India and, on the basis of these empirical findings, to draw some policy inferences for both changing societies and the developed West.
Gesehen am 22.06.2021